2020
DOI: 10.2147/ijwh.s235169
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of Health-Promoting Lifestyle in Pregnant Women Based on Pender’s Health Promotion Model</p>

Abstract: Background and Objectives: Pregnancy causes changes in women's lifestyle; therefore, their health-promoting behaviors should be improved in order to avoid problems during this critical period, which requires knowledge of the factors affecting these behaviors. This study was conducted to determine the predictors of health-promoting lifestyles in pregnant women based on Pender's health promotion model constructs.Methods: This descriptive study was carried out on 300 pregnant women in their second and third trime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
3
10
0
5
Order By: Relevance
“…Health-promoting lifestyles during pregnancy are important for alleviating maternal physical and mental stress (Bogaerts et al, 2013(Bogaerts et al, , 2017, maintaining optimal intrauterine environment and decreasing maternal and neonatal complications, for example preterm delivery, caesarean section, bleeding, maternal infection, obesity, hospitalisation, diabetes, low birth weight and early neonatal death (Ferrara et al, 2020;Oteng-Ntim et al, 2012;Procter & Campbell, 2014;Reijnders et al, 2019). It is evident that promoting healthy behaviours is cost effective as well as improving pregnant women's health (Jalili Bahabadi et al, 2020). However, no studies have explored the longitudinal changes of health-promoting behaviours throughout the pregnancy trimesters and the factors associated with longitudinal changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-promoting lifestyles during pregnancy are important for alleviating maternal physical and mental stress (Bogaerts et al, 2013(Bogaerts et al, , 2017, maintaining optimal intrauterine environment and decreasing maternal and neonatal complications, for example preterm delivery, caesarean section, bleeding, maternal infection, obesity, hospitalisation, diabetes, low birth weight and early neonatal death (Ferrara et al, 2020;Oteng-Ntim et al, 2012;Procter & Campbell, 2014;Reijnders et al, 2019). It is evident that promoting healthy behaviours is cost effective as well as improving pregnant women's health (Jalili Bahabadi et al, 2020). However, no studies have explored the longitudinal changes of health-promoting behaviours throughout the pregnancy trimesters and the factors associated with longitudinal changes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated associated factors of health‐promoting behaviours during pregnancy. Demographic and clinical characteristics of pregnant women were significantly associated with health‐promoting behaviours, for example maternal age, socioeconomic status, educational level, exercise habit and planned pregnancy (Gokyildiz et al, 2014; Goossens et al, 2016; Jalili Bahabadi et al, 2020; Lin et al, 2009; Yu et al, 2021). Self‐efficacy and maternal sense of coherence were also found positive associations with healthy behaviours (Lin et al, 2009; Shorey & Ng, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of social support, a supportive environment, and a socially well-functioning network for the physical and mental health of pregnant women is also emphasized by Jalili Bahabadi et al ( 2020 ). Moreover, in this study, the participants’ commitment seemed to grow when they realized that their contribution was valuable to others.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] Young, educated, and working mothers, due to their better socioeconomic status, are likely to have a greater and better understanding of the importance of their health and their impact on fetal health and more on their appearance and weight control and body mass index. [ 12 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is one of the most important natural and important stages of a woman's life, where the woman's body gradually undergoes certain physiological and anatomical changes during the stages of fetal development. [ 11 ] The hormonal, emotional, psychological, and physical factors specific to pregnancy cause changes in the physical, mental, social, and overall health dimensions of pregnant women during pregnancy[ 5 12 13 ] and easily affect and threaten their quality of life. [ 7 ] Therefore, this period is often a stressful period with physiological and psychological changes.…”
Section: Introductionmentioning
confidence: 99%